Climate change effects on the availability, potency, and conservation of African indigenous medicinal plants. A systematic literature review. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2026)
Background African indigenous medicinal plants play a critical role in primary healthcare, cultural heritage, and biodiversity conservation. However, climate change driven alterations in temperature, rainfall patterns, soil moisture, and fire regimes are increasingly threatening plant distribution, growth, and phytochemical integrity. The objective of this review was to synthesise existing evidence on the impacts of climate change on the availability, phytochemical composition, and conservation status of African indigenous medicinal plants. Methods A systematic literature review was conducted in accordance with PRISMA guidelines. Peer-reviewed studies published between 2000 and 2025 were retrieved from PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar. Search terms included climate change, medicinal plants, phytochemistry, traditional medicine, and Africa. Studies reporting climate-related effects on medicinal plant distribution, bioactive compound composition, harvesting pressure, or conservation status were included. Data were extracted and thematically synthesised across ecological, biochemical, and conservation dimensions. Results Sixty-two studies met the inclusion criteria. Most reported that rising temperatures, prolonged droughts, and shifting rainfall patterns have reduced the abundance and geographic range of key medicinal species, particularly in arid and semi-arid regions. Several studies demonstrated that climate-induced stress alters phytochemical profiles, often leading to reduced concentrations of bioactive compounds such as alkaloids, flavonoids, and essential oils. Increased harvesting pressure linked to declining availability further exacerbates extinction risks, especially for slow-growing and wild-harvested species. Conclusion Climate change is simultaneously reducing both the availability and therapeutic potency of African indigenous medicinal plants while increasing their vulnerability to overexploitation, posing serious risks to traditional healthcare systems and biodiversity conservation. Recommendations Climate-smart conservation approaches, targeted cultivation of high-value medicinal species, and systematic phytochemical monitoring should be integrated into national biodiversity, health, and climate adaptation policies.